Hermansky-Pudlak syndrome 2 — a novel mutation with factor VII deficiency: a fluke from India - Vibha Gupta; Rutvi Gautam Dave; Tulasi Geever; Sukesh C. Nair; Joy Mammen; N. A. Fouzia (Journal of Rare Diseases)
Abstract Objective Hermansky-Pudlak syndrome (HPS) is a rare autosomal recessive disorder characterized by oculocutaneous albinism and bleeding diathesis with other variable phenotypic features found in some of its subtypes, such as pulmonary fibrosis, colitis, or neutropenia. The disease is related to lysosome-related organelle dysfunction (LROs). There are 11 genetic subtypes of HPS (HPS1-HPS11). HPS was initially reported in Puerto Rico (HPS 1, 3) but has a worldwide prevalence of 1–9 per 1,000,000. The present case draws attention in three ways. First, it is the first case of HPS-2 reported from the Indian subcontinent, showing typical HPS-2-specific phenotypic features, including neutropenia and immunodeficiency with recurrent respiratory tract infections, and a novel homozygous AP3B1 mutation (c.2212delA, p.Arg738Glufs*38). Second, in addition to HPS-2, the subject also has Factor 7 heterozygous missense mutation (c.1151C>T, p.Thr384Met); lastly, a sibling (deceased) of the index case had phenotypic similarities to index case. An advanced workup of the present case was done, which included molecular techniques and platelet function studies by platelet aggregometry and flowcytometry and electron microscopy. Case A 5-year-old male from the state of Andhra Pradesh, India, presented with coarse facial features and silvery grey shine to his hair with complaints of recurrent episodes of fever with respiratory infections and ear infections since birth. He also had easy brusability and multiple episodes of epistaxis, treated with nasal packing and antifibrinolytics, bleeding on tooth extraction, and a few episodes of haematuria which required blood transfusion, and complete blood count showed neutropenia. Further examination revealed oculocutaneous albinism, pendular horizontal nystagmus, retinal pallor, significant iris transillumination, and abnormal pulmonary function study. Comprehensive laboratory tests were accomplished and ultimately detected pathogenic variants in two unrelated genes, AP3B1 and F7 — explaining the phenotype. Conclusion This case reports a rare case of Hermansky-Pudlak syndrome 2 from Indian subcontinent.